(untitled) (Communications in Computational Physics, 2018)
Focused transducers are frequently used in photoacoustic endoscopy (PAE) to ensure high acoustic resolution beyond the depth of optical diffraction. Although most transducers in PAE are ceramic and focus-fixed, we here propose the polyvinylidine fluoride (PVDF) based annular array to reduce the fabrication cost, and to allow dynamic focusing for increased depth of field. In this work, a method of direct lithography on the aluminum coated PVDF films was used for the annular array fabrication. The PVDF annular array was built with a 110 µm thick aluminum coated PVDF film, which contained three independent rings of equal width within a 5.5 mm aperture size. Phantom experiments were conducted for field test, and a simple linear model was used to compare the acquired results in the acoustic field test. The device was used for demonstration in PAE application. Potential applications of the proposed method include the PAE imaging of several large human organs and lumens such as the gastrointestinal tract and the cervical canal.